2015
DOI: 10.1038/ncomms9769
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous enhancements in photon absorption and charge transport of bismuth vanadate photoanodes for solar water splitting

Abstract: n-Type bismuth vanadate has been identified as one of the most promising photoanodes for use in a water-splitting photoelectrochemical cell. The major limitation of BiVO4 is its relatively wide bandgap (∼2.5 eV), which fundamentally limits its solar-to-hydrogen conversion efficiency. Here we show that annealing nanoporous bismuth vanadate electrodes at 350 °C under nitrogen flow can result in nitrogen doping and generation of oxygen vacancies. This gentle nitrogen treatment not only effectively reduces the ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
541
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(588 citation statements)
references
References 54 publications
42
541
3
2
Order By: Relevance
“…In contrast, ε xx was slightly different from ε zz in the case of intrinsic defective Bi 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 18 pristine and the intrinsic defective materials were 38.3 and 41.2, respectively. Those values are close to the experimentally reported one of 52, 48 and also very close to that obtained of 45.7 for anatase TiO 2 . 49 Here, let us simply remind that several studies mentioned that dielectric constant value greater than 10 is sufficient for good exciton dissociation to free c...…”
supporting
confidence: 92%
“…In contrast, ε xx was slightly different from ε zz in the case of intrinsic defective Bi 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 18 pristine and the intrinsic defective materials were 38.3 and 41.2, respectively. Those values are close to the experimentally reported one of 52, 48 and also very close to that obtained of 45.7 for anatase TiO 2 . 49 Here, let us simply remind that several studies mentioned that dielectric constant value greater than 10 is sufficient for good exciton dissociation to free c...…”
supporting
confidence: 92%
“…The BF 4 ‐treated MnO/BiVO 4 /WO 3 anode achieved 6.25 mA cm −2 at the 1.23 V versus RHE. We emphasize that the photocurrent of BF 4 ‐treated MnO attached to the BiVO 4 /WO 3 anode is the highest of the previously reported BiVO 4 ‐based photoanodes with hole scavenger for solar water splitting, as shown in Table S2 and Figure S4 (Supporting Information) 13, 14, 16, 17, 21, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69. Otherwise, Ca–EDTA‐treated MnO NPs/BiVO 4 /WO 3 recorded the lowest photocurrent density of about 2.5 mA cm −2 .…”
Section: Resultsmentioning
confidence: 70%
“…Therefore, most of the previously reported results related to BiVO 4 ‐based photoanodes13, 14, 16, 19, 47, 51, 52, 53 were measured in sulfite oxidation condition to show photo‐electrochemical properties of BiVO 4 ‐based electrodes independently of its poor water oxidation kinetics, as shown in Table S2 (Supporting Information). The photo‐electrochemical current densities of the BiVO 4 ‐based photoanodes4, 13, 14, 16, 17, 19, 20, 21, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 64, 65, 66, 67, 68, 69, 77 were plotted as a function of potential versus RHE. Thus, we measured PEC properties of BiVO 4 ‐based anodes under sulfite oxidation to figure out the effect of ligand engineering.…”
Section: Resultsmentioning
confidence: 99%
“…This was recently addressed by Kim et al, whose DFT PBE+U calculations also indicated the presence of deep level states associated with O vac defects in Bi-VO 4 . 49 In that work, they found that the negative ionization energy of O vac centers leads to spontaneous ionization to a 2+ charge state. However, it was determined that it is energetically favourable for these donated electrons to form small electron polarons via self-trapping at vanadium sites.…”
Section: Oxygen Vacancies In Bivomentioning
confidence: 98%